2011
DOI: 10.1111/j.1439-0507.2011.02132.x
|View full text |Cite
|
Sign up to set email alerts
|

Otomycosis in Shanghai: aetiology, clinical features and therapy

Abstract: Otomycosis is frequently seen in Shanghai and is a challenging problem due to recurrence and resistance to therapy. The aims of this study were to determine the pattern of fungal agents, sex distribution, clinical presentation, predisposing factors, complications and treatment outcomes of otomycosis. Retrospective review of 108 patients with a clinical diagnosis of otomycosis treated from September 2009 to September 2010 in otolaryngology outpatient department. It has been found to be more prevalent in female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
53
9
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 24 publications
12
53
9
2
Order By: Relevance
“…While some studies have reported otomycosis to be more common among young men [1, 5, 7, 8, 15] as in our series, many others have reported it to be so among young females [2, 3, 14, 16, 17]. In our series the male : female ratio was 1.7 : 1.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…While some studies have reported otomycosis to be more common among young men [1, 5, 7, 8, 15] as in our series, many others have reported it to be so among young females [2, 3, 14, 16, 17]. In our series the male : female ratio was 1.7 : 1.…”
Section: Discussioncontrasting
confidence: 59%
“…Obsessive manipulation of the external ear with any hard objects such as wooden sticks or metal wax picks to clean the ear of wax and vigorous rubbing of the ears for relief from itching (in case of otalgia due to eustachian catarrh, serous otitis, or acute otitis media) is a common practice. These practices may cause trauma (usually minor and hence unnoticed) to the skin of external auditory canal and deposition of fungal conidia in the wound leading to fungal infection [17]. The moisture, warmth, and acidic pH of the external auditory canal provide ideal growth requirements for the fungi.…”
Section: Discussionmentioning
confidence: 99%
“…This disease is well prevalent in people coming from rural area surrounding our institution. There is a female predominance (59 %) in our study, which well correlates with the studies by Jia X [15] and Yehia MM [16]. The most common presenting complaint in our study is ear pain, which is same in Tang Ho study [10], but Kurshid Anwar coded hearing loss as the most common presentation in otomycosis [17].…”
Section: Discussionsupporting
confidence: 89%
“…2 Clinical examination usually shows grayishwhite and black or cheese-like thick debris and inflammation of the outer ear. [3][4][5][6][7][8] Prevalence of disease was more in young adults with female predominance. The predisposing factors included wearing head clothes, hot weather, presence of dermatomycoses, dusty working environment and swimming.…”
Section: Introductionmentioning
confidence: 99%